Mesoderm/mesenchyme homeobox gene l promotes vascular smooth muscle cell phenotypic modulation and vascular remodeling. (15th January 2018) - Wu, Bing; Zhang, Lei; Zhu, Yun-He; Zhang, You-en; Zheng, Fei; Yang, Jian-Ye; Guo, Ling-Yun; Li, Xing-Yuan; Wang, Lu; Tang, Jun-Ming; Chen, Shi-You; Wang, Jia-Ning
Abstract: Aims: To investigate the role of mesoderm/mesenchyme homeobox gene l (Meox1) in vascular smooth muscle cells (SMCs) phenotypic modulation during vascular remodeling. Methods and results: By using immunostaining, Western blot, and histological analyses, we found that Meox1 was up-regulated in PDGF-BB-treated SMCs in vitro and balloon injury-induced arterial SMCs in vivo. Meox1 knockdown by shRNA restored the expression of contractile SMCs phenotype markers including smooth muscle α-actin (α-SMA) and calponin. In contrast, overexpression of Moex1 inhibited α-SMA and calponin expressions while inducing the expressions of synthetic SMCs phenotype markers such as matrix gla protein, osteopontin, and proliferating cell nuclear antigen. Mechanistically, Meox1 mediated the SMCs phenotypic modulation through FAK-ERK1/2 signaling, which appears to induce autophagy in SMCs. In vivo, knockdown of Meox1 attenuated injury-induced neointima formation and promoted SMCs contractile proteins expressions. Meox1 knockdown also reduced the number of proliferating SMCs, suggesting that Meox1 was important for SMCs proliferation in vivo. Moreover, knockdown of Meox1 attenuated ERK1/2 signaling and autophagy markers expressions, suggesting that Meox1 may promote SMCs phenotypic modulation via ERK1/2 signaling-autophagy in vivo. Conclusion: Our data indicated that Meox1 promotes SMCs phenotypic modulation and injury-induced vascular remodeling by regulating the FAK-ERK1/2-autophagy signaling cascade. Thus, targeting Meox1 may be an attractive approach for treating proliferating vascular diseases.